Analysis of higher order thinking skills and lower thinking skill items in summative evaluation of Akidah-Akhlak learning - Emi Mustaqimah (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
This research explores the implementation of summative evaluation in Islamic Religious Education (Akidah Akhlak) subjects at SMP Muhammadiyah 4 Yogyakarta, with a focus on implementing Higher Order Thinking Skills (HOTS). Summative evaluation is considered very important in measuring the achievement of the Islamic Religious Education program. High-level critical and creative thinking skills (HOTS) are considered important in solving everyday problems, especially in the era of globalization. This research uses a qualitative descriptive method with document content analysis, especially the final semester assessment questions for Aqidah Akhlak class VII made by the Regional Leadership of Muhammadiyah (PWM) DIY. The findings show that of the 12 final semester assessment questions, 6 questions (15%) meet the HOTS criteria, while 28 questions (70%) fall into the low-level thinking ability (LOTS) category. In addition, 6 items (15%) did not have a correct answer among the available options. These findings underscore the need to increase the integration of HOTS in designing summative evaluation questions for Islamic Religious Education (PAI). This research aims to describe and collect information about the implementation of summative evaluations and assess the results at SMP Muhammadiyah 4 Yogyakarta. Effective summative evaluation is expected to make a significant contribution to improving the quality of Islamic education at the secondary level.